Political spillovers of workplace democracy in Germany - Uwe Jirjahn; Thi Xuan Thu Le (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2022)
While works councils provide a highly developed mechanism to promote workplace democracy, research on their consequences has been dominated by economic aspects. This study brings a new perspective to the understanding of works councils by examining their influence on workers' political behavior. Political spillover theory suggests that participation in the firm's decision making has the potential to foster workers' political participation in civic society. Our study for Germany indeed finds a positive association between the presence of a works council and workers' interest in politics. This holds in panel data estimations including a large set of controls and accounting for unobserved individual-specific factors. However, separate estimations by gender show a positive association between works councils and political interest only for men, but not for women. Traditional gender roles may make it difficult for women to be politically engaged even when a works council is present.
Keywords: J51; J52; J53; J58; 330; Works council; works councilor; union member; gender; political interest